On the congestion control in Optical Burst Switching networks - Abid, A.; Abbou, F. M.; Ewe, Hong Tat (IEEE, 2007)
Optical Burst Switching (OBS) is a promising switching paradigm that is very suitable to be deployed in the next generation Internet. OBS combines the benefits of various evolving techniques to economize the network traffic through an optical network. However, OBS lacks mechanisms to prevent or eliminate the network traffic congestion. In this paper, we propose to use the Flow Control and Reservation Bits (FCRB) of the Staged Reservation Scheme (SRS) as a congestion control mechanism for optical burst switched networks. The simulation results show that this technique allows the OBS edge nodes to control the network traffic flows, and enables the core nodes to maintain a low burst drop rate.